Nxopaxopo wa vutlhokovetseri byo phofula bya J.M Magaisa - Ringani, G. N. (University of Limpopo, 2014)
The main aim of this study is to evaluate protest poetry in Mihloti (1981) and Xikolokolo nguvu ya Pitori (1987) by J.M. Magaisa with special references to theme, subject matter and the use of figures of speech.. Chapter 1 indicates the aim of the study, motivation, statement of the problem, research methodology, literature review and the key concepts which are used in this research. Chapter 2 explains the themes of the protest poetry in Magaisa’s poetry. In some explanation of the themes, some of the figures of speech have been used with the aim of making readers to understand his poetry. Chapter 3 indicates the modes of expression in Magaisa’ protest poetry. Some of the figures of speech and difficult terms have been explained in this chapter make people to understand them. Chapter 4 is the general conclusion which indicates the findings of the research and recommendations for further researches.
Poetry protest by J.M Magaisa
Thesis (M.A. (African Languages)) --University of Limpopo, 2014
Keywords: Protest poetry; Tsonga (African People); Protest literature, South African; Poetry -- History and criticism; South African Literature